METODOLOGIA PARA ADAPTAÇÃO DE EDIFÍCIOS EXISTENTES PARA GREEN BUILDINGS SEGUINDO OS PARÂMETROS DO UI GREENMETRICS - GUILHERME DE SOUZA SILVA (2022)
Today's society has shown an increasing concern with environmental and sustainability issues. The scarcity of resources and, also, the mismanagement of them, makes the institutions increasingly search for ways, not only to optimize their use, but also to change the behavior of society as a whole. Higher Education Institutions (HEIs) have shown increasing potential for the development of studies that serve as a test for application on a larger scale, such as the city or state in which they are located. Seeking an answer to the resource questions and due to this potential and also the power that HEIs have to influence the environment in which they are inserted, some rankings have been adopted to measure the sustainability of universities, such as the UI GreenMetrics Word University Ranking. developed by the Indonesian University, and already applied in more than 900 institutions. With this, this work has the proposal to create a methodology to adapt traditional buildings of the Federal University of Mato Grosso do Sul - UFMS to green buildings, or Green Building, following the metrics of the UI GreenMetric Ranking. As a result, there is the creation of the Adaptation Methodology, the Green Seal – UFMS's own seal for metrification of blocks and, finally, some dissemination policies. Keywords: Green building, automation, Internet of Things, Energy Efficiency.